On the Sources and Value of Information: Public Announcements and Macroeconomic Performance. - Myatt, D; Wallace, C (Department of Economics (University of Oxford), 2008)
In the context of macroeconomic coordination, studies of the social value of information distinguish sharply between private and public information. However, no information is truly public (that is, common knowledge) or private in the established sense. This paper develops a general approach by allowing for many informative signals each of which incorporates elements of both public and private information. A measure of relative publicity determines a signal's equilibrium use and its social value. Output gaps (and hence social losses) arise when signals differ in their publicity: such differences drive a wedge between price-formation and expectations-formation processes. Turning to the effect of public announcements, and contrary to previous results, it is never socially optimal to withhold information completely, nor is it optimal to release perfectly public (or, indeed, perfectly private) information. Instead, when perfect communication is feasible, limited clarity enhances macroeconomic performance.